The Management of Shipyard in Bungus Fishing Port West Sumatera Province - Riza, Femi; Syaifuddin, Syaifuddin; Nofrizal, Nofrizal (Jurnal Online Mahasiswa (JOM) Bidang Perikanan dan Ilmu Kelautan, 2018)
ABSTRACT This research is conducted on 11-18 December 2017 inBungus Fishing Port, West Sumatra Province. The object of research is a shipyard in Bungus Fishing Port which is aimed to describe the management of shipyard in Bungus Fishing Port. The method used in this research is survey method during the process of collecting data. As information, the shipyard in Bungus Fishing Port is owned by government and specifically focused in maintenance and repair. This shipyard also using vessel lift type dock. The shipyard in Bungus Fishing Port also supported the fishing vessel and non-fishing vessel with maximum weight up to 30 GT and main material consisted from wood and fiber. The shipyard in Bungus is categorized as traditional shipyard. From the appliance that used during the maintenance and repair, this shipyard encountering several problem which are the limited production of new ship and the lack of dock facility. This problem caused by the lack of the worker ability in making new ship due to the rare of training and inappropriate of docks size as area for building new ship. These problems can be seen as the obstacles in the modernization and development of the shipyard in Bungus Fishing Port. Keywords: Management, Shipyard, Bungus Fishing Port